Model and Simulation of Deep-Bed Clove Drying Effect of Fermented Treatment - Agus Supriatna Somantri (PERTETA, 2001)
This paper describes the prediction of deep-bed clove drying. This model also considers mass and heat profile that was affected by fermentation process. This model used the equation of two-dimensional finite difference approximation. The dynamic of two-dimensional equation were solved numerically by alternating direction Crank-Nicolson method and then applied to simulate the changes of moisture content and temperature of cloves during drying process. The capabilities of these models were compared with experimental data obtained from the research under variable conditions such as temperature and relative humidity on fermentation and non-fermentation treatment of cloves. The result of simulation showed that the equilibrium of moisture content (EMC) wasconsiderably decreased whereas the rate of drying was dramatically increased with the increase of the temperature of drying. The profile of moisture content on deep-bed cloves drying was unique. The fermented and non-fermented treatments of the cloves did not give significant differences on the drying time in order to achieve the equilibrium of moisture content.